2007
DOI: 10.1111/j.1399-3062.2007.00220.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemically proven cytomegalovirus end‐organ disease in solid organ transplant patients: clinical features and usefulness of conventional diagnostic tests

Abstract: We studied the main clinical features, outcome, and laboratory parameters in a group of solid organ transplant (SOT) patients with immunohistochemically proven cytomegalovirus (CMV) disease. Confirmed CMV cases were obtained through databases. Demographics, clinical data, transplantation type, immunosuppressive regimens, donor and recipient CMV serostatus, therapy, outcome and laboratory results, pp65 antigenemia, and qualitative polymerase chain reaction (PCR) for CMV were analyzed. From 1995 to 2004, 31 case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 21 publications
0
33
0
1
Order By: Relevance
“…In the current era, gastrointestinal CMV disease constitutes the vast majority of tissueinvasi ve cases [3,7,20] , and in a number of cases, especially in CMV R+ patients, this type of CMV disease is "compartmentalized." In a retrospective study, the sensitivity of pp65 antigenemia assay (defined as detection of ≥ 1 positi ve cells/2 ×10 5 leukocytes) for diagnosis of CMV gastrointestinal disease was only 54% [82] .…”
Section: Treatment Of Compartmentalized CMV Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…In the current era, gastrointestinal CMV disease constitutes the vast majority of tissueinvasi ve cases [3,7,20] , and in a number of cases, especially in CMV R+ patients, this type of CMV disease is "compartmentalized." In a retrospective study, the sensitivity of pp65 antigenemia assay (defined as detection of ≥ 1 positi ve cells/2 ×10 5 leukocytes) for diagnosis of CMV gastrointestinal disease was only 54% [82] .…”
Section: Treatment Of Compartmentalized CMV Diseasementioning
confidence: 99%
“…These have been traditionally categorized either as CMV syndrome (fever with bone marrow suppression) and tissueinvasi ve CMV disease (which may involve virtually any organ system) [6] . The most common organ system involved during CMV disease is the gastrointestinal tract (in the form of CMV gastritis, esophagitis, enteritis, and colitis), accounting for over 70% of tissueinvasi ve CMV disease cases in solid organ transplant recipients [7] . The transplanted liver also seems to be more predisposed to develop tissueinvasion by CMV such that CMV hepatitis occurs more frequently in liver transplant recipients than in other solid organ transplant recipients.…”
Section: Direct CMV Effectsmentioning
confidence: 99%
“…2 Although CMV peritonitis also has been reported after solid-organ transplant, it is rare and mostly associated with gut perforation. In a series of CMV infections after solid-organ transplanted patients from Spain, 2 cases of peritonitis were reported but 6 Another series of 3 patients with CMV-associated peritonitis were reported after renal transplant, but all had sigmoid perforation documented on laparotomy. 7 There is one report of CMV peritonitis without gut perforation after renal transplant in a patient who was previously on peritoneal dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…The antigenemia assay is one of the most widely used methods for detecting reactivation of CMV infection, but only a few studies have examined its diagnostic value for CMV-GID, [18][19][20][21] and all were retrospective in design. Jang et al 20 recently reported that the sensitivity and specificity of the CMV antigenemia assay for the diagnosis of CMV-GID were 54% and 88%, respectively, in patients with secondary immunodeficiency disease.…”
Section: Discussionmentioning
confidence: 99%